2019
DOI: 10.3389/fphar.2019.01460
|View full text |Cite
|
Sign up to set email alerts
|

Sotetsuflavone Induces Autophagy in Non-Small Cell Lung Cancer Through Blocking PI3K/Akt/mTOR Signaling Pathway in Vivo and in Vitro

Abstract: Non-small cell lung cancer (NSCLC) is a globally scaled disease with a high incidence and high associated mortality rate. Autophagy is one of the important physiological activities that helps to control cell survival, influences the dynamics of cell death, and which plays a crucial role in the pathophysiology of NSCLC. Sotetsuflavone is a naturally derived and occurring flavonoid, and previous studies have demonstrated that sotetsuflavone possesses potential anti-cancer activities. However, whether or not sote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Numerous natural products have been proved to suppress cancer cells by targeting the PI3K/AKT/mTOR-mediated autophagy ( 53 ). Wang et al found a natural source of flavonoid, sotetsuflavone, which could induce autophagy by blocking PI3K/AKT/mTOR pathways in NSCLC cells ( 54 ). Besides, the PI3K/AmKT/mTOR signaling pathway is involved in the regulation of inflammation, which is usually related to the activation of TLRs/NF-κB, cytokine receptor and tyrosine kinase receptor signals ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous natural products have been proved to suppress cancer cells by targeting the PI3K/AKT/mTOR-mediated autophagy ( 53 ). Wang et al found a natural source of flavonoid, sotetsuflavone, which could induce autophagy by blocking PI3K/AKT/mTOR pathways in NSCLC cells ( 54 ). Besides, the PI3K/AmKT/mTOR signaling pathway is involved in the regulation of inflammation, which is usually related to the activation of TLRs/NF-κB, cytokine receptor and tyrosine kinase receptor signals ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ganoderic acid DM provokes autophagic apoptosis by repressing the PI3K/Akt/mTOR signaling in NSCLC cells ( 29 ). Sotetsuflavone promotes autophagy in NSCLC cells by inhibiting PI3K/Akt/mTOR axis in vitro and in vivo ( 30 ). An active drug sensitizing agent improves gefitinib therapy by up-regulating autophagy and down-regulating PI3K/Akt/mTOR signaling in NSCLC ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibiting the proliferation and inducing apoptosis of lung cancer has become a feasible strategy for the treatment of lung cancer. A large number of studies have also found that mechanisms of many natural anticancer drugs against lung cancer are related to the regulation of different signaling pathways to inhibit the proliferation of lung cancer cells and induce the apoptosis of lung cancer cells ( Wang S. et al., 2019 ; Han et al., 2020 ; Hu et al., 2020 ). Therefore, we subsequently designed corresponding in vitro experiments in order to prove the prediction results of network pharmacology.…”
Section: Discussionmentioning
confidence: 99%